Assessing the urban sustainable development strategy: An application of a smart city services sustainability taxonomy - Ana Jane Benites (Elsevier, 2021)
This article contextualizes the smart cities paradigm in the panorama of contemporary city challenges, which increasingly encompasses the pursuit of sustainable development goals and the need to incorporate urban resilient behaviors, mainly in response to the impacts of climate change. Such a scenario also comprises the interpretation of smart cities as tools to assist policymakers and city administrators in directing solutions based on emerging information and communication technologies (ICTs) to the materialization of urban strategic plans addressing these confrontations. There are, however, no established indicator systems that attest to the substantiation of such plans by smart city solutions, nor to their alignment with the goals of urban sustainable development. Therefore, an analytical framework is proposed here to address this knowledge gap. It enables guiding the leverage of smart cities’ ICTs, not only for the achievement of economic goals, a feature intrinsic to smart city innovations, but also to reach other sustainability dimensions, as the environmental, social, institutional and cultural. To this end, generic sustainability indicator frameworks and also a set of smart city indicators are explored. They are examined as potential sources of specific taxonomies in smart city services for urban sustainable development. From this compilation of options, the Dashboard of Sustainability, once one of the indicator systems most recommended by experts, is revisited. It is adapted as a framework for analyzing and helping to maintain the strategic targeting of smart city solutions, during their entire lifecycle, at sustainability. To complete the qualitative-analytical-taxonomic frame, the services offered by a real smart city solution, the Rio de Janeiro Center of Operations, are employed as a model. This allows investigating its 9-year transition from a wider, larger capacity, strategic and innovative configuration in orientation towards sustainability perspectives, to a more narrow, operational composition, that is predominantly devoted to the economic dimension.